Sorafenib and triptolide loaded cancer cell-platelet hybrid membrane-camouflaged liquid crystalline lipid nanoparticles for the treatment of hepatocellular carcinoma - Zhe Li (BMC, 2021)
Abstract In addition to early detection, early diagnosis, and early surgery, it is of great significance to use new strategies for the treatment of hepatocellular carcinoma (HCC). Studies showed that the combination of sorafenib (SFN) and triptolide (TPL) could reduce the clinical dose of SFN and maintain good anti-HCC effect. But the solubility of SFN and TPL in water is low and both drugs have certain toxicity. Therefore, we constructed a biomimetic nanosystem based on cancer cell-platelet (PLT) hybrid membrane camouflage to co-deliver SFN and TPL taking advantage of PLT membrane with long circulation functions and tumor cell membrane with homologous targeting. The biomimetic nanosystem, SFN and TPL loaded cancer cell-PLT hybrid membrane-camouflaged liquid crystalline lipid nanoparticles ((SFN + TPL)@CPLCNPs), could simultaneously load SFN and TPL at the molar ratio of SFN to TPL close to 10:1. (SFN + TPL)@CPLCNPs achieved long circulation function and tumor targeting at the same time, promoting tumor cell apoptosis, inhibiting tumor growth, and achieving a better "synergy and attenuation effect", which provided new ideas for the treatment of HCC. Graphical Abstract